Pendekatan Teori Keperawatan Betty Neuman Dalam Pengkajian Keperawatan Kesehatan Komunitas Tentang COVID-19 Di Masyarakat Kebumen - Marsito (STIKes Payung Negeri Pekanbaru, 2021)
The amount of statistical data is increasing day by day, this needs to be anticipated for people's behaviour to live clean and healthy, such as washing hands, wearing masks, and maintaining distance. This behaviour can be carried out by a Betty Neument community nursing assessment with a Community as Partner approach. This article describes the behaviour of the COVID-19 community, core data, environment, health services, transportation, and recreation safety. Methods: The study used an analytical descriptive evaluation approach describing the behaviour of the community during the COVID-19 pandemics. The data was collected using a google form to the participating Kebumen community. It was written that the confidentiality of the sample was maintained by randomized families who wanted to provide information on COVID-19 with an Android mobile phone, the number of samples participating was 120 people. Research results: For the core data age as respondents 41-60 years 66 families (54%), male sex 94 families (79%), high school education 48 families (40%). Home environment 98 families (82%) always maintain the cleanliness of the residence, in a densely populated 54 families (45%). Meanwhile, health services sprayed sometimes 61 families (51%), who participated in health counselling 46 families (38%). Safety transportation wearing masks 22 families (18%), always leaving the house doing geographic mobilization of families there were 46 families (38%). Family recreation activities during the COVID-19 pandemic held a gathering of 2 families (2%), visiting out of town to a family place where there were 13 families (11%). The assessment using the Betty Neument method with the Community as Partner approach can be used to see the healthy behaviour of COVID-19.